Memanfaatkan Whatsapps Business untuk Promosi dan Penjualan - Handijono, Ardijan; Gunarto, Rudy Irawan; Sutrisna, Entis (Perhimpunan Sarjana Ekonomi dan Bisnis, 2024)
In the digital era, communication has become easier and faster thanks to existing technological advances. Various digital platforms, such as social media, instant messaging applications, or email, allow people to communicate easily without being constrained by time and distance. Online marketing can be done through various digital platforms such as WhatsApps, Websites, social media, email and other online advertising platforms. One of the most popular instant massages at the moment is WhatsApp and one specifically intended for business is WhatsApp Business. This application allows businesses to interact with customers directly via the WhatsApp platform. Warung Jajan Amak Apak, which is located in the Depok area, sells various grilled snacks and several fresh drinks to customers from residents around the stall. After conducting several discussions and questions and answers, it was discovered that this MSME had not used a marketing strategy, its business reach was also limited to the area around the place of business so that its sales turnover could not increase significantly. For this reason, on this occasion we will conduct training on the use of WhatsApp Business to increase sales. There are several approaches that we use, namely presentations, questions and answers and discussions, as well as assistance on how to use WhatsApp Business for promotions and increasing sales. After this PKM activity, it is hoped that partners will be able to use WhatsApp Business as a cheap and effective promotional tool, to introduce their products and expand their sales reach, thereby increasing business and business profits.